Seroprevalence of brucellosis and leptospirosis in urban citizens with backyard breeding in the district of José Leonardo Ortiz, Chiclayo - Yamunaqué-Castro, Luis A. (2020)
Objective: To describe the seroprevalence of and risk factors for brucellosis and leptospirosis in urban citizens with backyard breeding in the district of José Leonardo Ortiz, Chiclayo. Methods: Cross-sectional study including 90 citizens during the month of October and December of 2016. IgM and IgG specific antibodies for brucellosis and leptospirosis were determined using the indirect ELISA method. Factors associated with these diseases were gathered using a structural survey. Results: The seroprevalence of brucellosis and leptospirosis was 2.2% and 28.9%, respectively. The most common environmental features of the population were that 73.3% use latrines 83.3% had contact with stagnant water and 62.2% had contact with rodents. No association between the variables looked for and these two diseases were found. Conclusions: We found a high seroprevalence of leptospirosis but a low prevalence of brucellosis in this setting. We suggest performing longitudinal studies that may identify risk factors to prevent these diseases.